Russia pivot to (Southeast) Asia. Russia’s Policy Towards Southeast Asia in the 21st Century - Pietrasiak, Małgorzata (2022)
The title of the book refers to a slogan that emerged in the political debate at the beginning of the second decade of the 21st century. The slogan is provocative because, on the one hand, it paraphrases the American return to Asia (US pivot to Asia) and, on the other hand, it recalls not only Russia’s geographical but also political presence in Asia. For Russia, the region of Northeast Asia remains the most important for security reasons, but in the second decade of the 21st century, the region of Southeast Asia became increasingly active. The ASEAN countries developed rapidly and implemented a number of measures to promote closer integration. The growing importance of Southeast Asia has prompted Russia to develop a strategy for this sub-region. It is part of Russia’s broader geopolitical game and must be seen in terms of establishing a balance between the major regional powers of the US, China, Japan and India on the one hand, and seeking a place of its own on the “chessboard. ” The main areas of cooperation with ASEAN are security and arms trade, energy and energy raw materials. Despite all the declarations, economic and trade cooperation has been slow. An example of the latest initiative proposed by President Vladimir Putin is the Greater Eurasian Partnership. I consider the initiative to be unrealistic at this stage, particularly given Russia’s economic constraints, even though diplomatic efforts are under way. In this case, the Chinese factor remains uncertain, as Greater Eurasia refers geographically to the Chinese Belt and Road Project. Russia’s most important partner in the region remains Vietnam, while Singapore, Indonesia, Thailand and Malaysia are among the major trading partners. The analysis was based on international developments up to the end of the second decade of the 21st century.
Keywords: International relations; Russia; ASEAN; Southeast Asia; multilateral and bilateral diplomacy